A guide for effective anatomical vascularization studies: useful ex vivo methods for both CT and MRI imaging before dissection. Issue 1 (11th October 2017) - Renard, Yohann; Hossu, Gabriela; Chen, Bailiang; Krebs, Marine; Labrousse, Marc; Perez, Manuela
Abstract: The objective of this study was to develop a simple and useful injection protocol for imaging cadaveric vascularization and dissection. Mixtures of contrast agent and cast product should provide adequate contrast for two types of ex vivo imaging (MRI and CT) and should harden to allow gross dissection of the injected structures. We tested the most popular contrast agents and cast products, and selected the optimal mixture composition based on their availability and ease of use. All mixtures were first tested in vitro to adjust dilution parameters of each contrast agent and to fine‐tune MR imaging acquisition sequences. Mixtures were then injected in 24 pig livers and one human pancreas for MR and computed tomography (CT) imaging before anatomical dissection. Colorized latex, gadobutrol and barite mixture met the above objective. Mixtures composed of copper sulfate (CuSO4 ) gadoxetic acid (for MRI) and iodine (for CT) gave an inhomogeneous signal or extravasation of the contrast agent. Agar did not harden sufficiently for gross dissection but appears useful for CT and magnetic resonance imaging (MRI) studies without dissection. Silicone was very hard to inject but achieved the goals of the study. Resin is particularly difficult to use but could replace latex as an alternative for corrosion instead of dissection. This injection protocol allows CT and MRI images to be obtained of cadaveric vascularization and anatomical casts in the same anatomic specimen. Post‐imaging processing software allow easy 3D reconstruction of complex anatomical structures using this technique. Applications are numerous, e.g. surgical training, teaching methods, postmortem anatomic studies, pathologic studies, and forensic diagnoses.